Formulation of Essential Oil-based Air Freshener Gel - Phuong, Luu Ly Cat; Tai, Diep The; Hoang, Nguyen Minh; Tran, Nguyen Thi Thao (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 4DO - 10.25073/2588-1140/vnunst.5432, 2022)
Meanwhile, many reports of health risks caused by chemical or volatile organic compounds from gel air fresheners, odour removal products have been found, and their wide range of applications continues present in daily life. Therefore, the essential oil-based gel air freshener, a safe and available price product for the consumer and for human health protection, was studied and formulated with natural gelling agents (carrageenan, xanthan gum), natural fragrances (essential oils and aroma extracts), a surfactant (polysorbate 20), co-solvent (ethylene glycol), sodium benzoate, sodium chloride, and distilled water at varying concentrations. The essential oils extracted from pomelo peels, and aerial parts of lemongrass and peppermint acted both as flavoring agents and antimicrobial agents. Scent formulas of D-JA, D-PO, and D-FV blended from natural fragrances were conducted on the various gel formulas (I, II, and III). The most significant product samples were given by formula I (D-PO) being recorded at 0.0121 of specific gravity, a syneresis rate of 18.91%, and pH 4.88. This formula met the given criteria and panellists. Additionally, the formulas of air freshener gels containing essential oils as bioactive compounds presented antibacterial activity against Escherichia coli and Staphylococcus aureus ., especially the formula with lemongrass essential oils and blended essential oils. These results indicated that essential oils on air freshener gel can inhibit the growth of bacteria and are safe for the consumer.